On understanding data scientists - Pereira, Paula (2020)
Data is everywhere and in everything we do. While,on its own, data has little value, its analysis under the lenses ofdata science currently supports extremely valuable functions andsystems. In recent years, the need to obtain knowledge from hugeamounts of data lead companies to hire many professionals ableto work creatively on data for data science position, regardlessof their academic and professional background. Our analysisof the collected information allowed us to conclude that thereis still a need to distinguish professionals concerning their pastexperiences, since they impact the way they perform data sciencetasks and the technologies they use. The results of this researchare particularly useful for the scientific community and theindustry in the design of solutions that are effectively useful toall data science workers